A Short review on wrought austenitic stainless steels at high temperatures: processing, microstructure, properties and performance - Plaut,Ronald Lesley (2007)
Wrought austenitic stainless steels are widely used in high temperature applications. This short review discusses initially the processing of this class of steels, with emphasis on solidification and hot working behavior. Following, a brief summary is made on the precipitation behavior and the numerous phases that may appear in their microstructures. Creep and oxidation resistance are, then, briefly discussed, and finalizing their performance is compared with other high temperature metallic materials.